Characterizing Ethereum's Mining Power Decentralization at a Deeper Level - Zeng, Liyi; Chen, Yang; Chen, Shuo; Zhang, Xian; Guo, Zhongxin; Xu, Wei; Moscibroda, Thomas (IEEE Conference on Computer Communications (INFOCOM), 2021)
For proof-of-work blockchains such as Ethereum, the mining power decentralization is an important discussion point in the community. Previous studies mostly focus on the aggregated power of the mining pools, neglecting the pool participants who are the source of the pools’ power. In this paper, we present the first large-scale study of the pool participants in Ethereum’s mining pools. Pool participants are not directly observable because they communicate with their pools via private channels. However, they leave “footprints” on chain as they use Ethereum accounts to anonymously receive rewards from mining pools. For this study, we combine several data sources to identify 62,358,646 pool reward transactions sent by 47 pools to their participants over Ethereum’s entire near 5-year history. Our analyses about these transactions reveal interesting insights about three aspects of pool participants: the power decentralization at the participant level, their pool-switching behavior, and why they participate in pools. Our results provide a complementary and more balanced view about Ethereum’s mining power decentralization at a deeper level.